A rapid antigen test to detect adenosine deaminase 2 (ADA2) in biological fluids and its application in clinical diagnostics - Yang, Weiping; Zhou, Qing; Porcel, Jose M.; Wang, Jun; Wu, Chengxiang; Zavialov, Andrey V. (Frontiers in Immunology, 2025)
IntroductionSaliva biomarkers provide a convenient and noninvasive method for diagnosing immune and genetic disorders. One such biomarker is adenosine deaminase 2 (ADA2), an enzyme that converts adenosine into inosine and is elevated in cancer and immune diseases. Currently, ADA2 activity can be used to diagnose pleural tuberculosis. Recently, we developed an ELISA assay that detects ADA2 in saliva. This test has been successfully employed to diagnose adenosine deaminase 2 deficiency (DADA2) and potentially to identify individuals with head and neck cancer. DADA2 is a rare genetic disease that can lead to systemic vasculitis, early onset stroke, bone marrow failure, and/or immunodeficiency. A rapid, simple, and affordable point-of-care (POC) test would significantly aid in diagnosing DADA2 and facilitate appropriate treatment.MethodsIn this study, we created a novel colloidal gold-based immunochromatographic strip (ICS) containing polyclonal antigen-purified anti-ADA2 antibodies. The ADA2 rapid antigen test (RAT) was calibrated precisely to detect ADA2 in the saliva of healthy individuals, while those with ADA2 deficiency received negative results.ResultsThe test successfully confirmed DADA2 in nine patients with different pathogenic mutations in ADA2, while 58 of 59 healthy donors tested positive for ADA2. DiscussionThe ADA2 rapid antigen test reliably screens patients with autoimmune disorders, accurately diagnosing DADA2. This test can also be used to diagnose pleural tuberculosis or other diseases with significantly elevated ADA2 levels.